Bank's Position as a Holder of Lien Objects Confiscated By The State From a Public Interest Perspective - Ulfanora; Tasman (LPPM Universitas Ekasakti, 2026)
Banking plays a strategic role in supporting national development through its financial intermediation function. One of the main instruments in banking activities is collateral, which provides legal certainty for creditors. However, problems arise when the collateral is seized by the state in corruption cases. The conflict between the bank's right of execution as the creditor holding the collateral and the state's interest in recovering assets resulting from corruption creates legal uncertainty that has a systemic impact on public trust in the banking sector. One form of uncertainty regarding bank collateral is the ease with which the state can seize the collateral for reasons of public interest. In this case, banks lack legal protection and strong legal certainty as the separatist party holding the collateral. The research results show, first, that Supreme Court Regulation Number 2 of 2022 concerning Procedures for Resolving Objections from Good-Faith Third Parties to Decisions on Confiscation of Property Not Owned by the Defendant in Corruption Cases does not provide adequate protection for banks because it only accommodates third parties with physical ownership of the assets. Furthermore, Supreme Court Decision No. 540 K/Pdt/2022 reinforces the tendency to prioritize state interests, weakening the legal position of banks as collateral holders. As agents of development, banks have a public interest that should be protected by law to maintain national economic stability. Therefore, regulatory reform is needed that explicitly recognizes banks as third parties acting in good faith in the Banking Law. Furthermore, the position of banks as collateral holders in Law Number 4 of 1996 concerning Mortgage Rights needs to be explicitly regulated by adding a norm or paragraph to Article 9 in Part III concerning Grantors and Holders of Mortgage Rights. Furthermore, there needs to be an exception in the Corruption Crime Law regarding the seizure of tangible and intangible movable assets that have become collateral objects by banks. This way, there is legal certainty for banks as creditors with separatist rights over material objects, allowing them to directly execute their collateral objects without the need for asset seizure by the state.